A Lean Start-up approach for developing minimum viable products in an established company. Issue 3 (3rd July 2019) - Dennehy, Denis; Kasraian, Laleh; O'Raghallaigh, Paidi; Conboy, Kieran; Sammon, Dave; Lynch, Patrick
ABSTRACT: The minimum viable product (MVP) is a fundamental concept of the Lean Start-up approach as it enables a company to quickly start the learning process by integrating feedback from early adopters. Although the MVP concept has evolved over the years, its application is most often reported in a start-up context, even though established companies struggle to develop MVPs. This study reports on the experience and lessons learned at Texuna, an established company, where the software product innovation team created a process map for developing MVPs. This is the first study that allows the original MVP approach to be extended and applied to established organisations.